Ice Nucleation Activity and Aeolian Dispersal Success in Airborne and Aquatic Microalgae - Tesson, Sylvie V. M.; Šantl-Temkiv, Tina (Frontiers in Microbiology, 2018)
Microalgae are common members of the atmospheric microbial assemblages. Diverse airborne microorganisms are known to produce ice nucleation active (INA) compounds, which catalyze cloud and rain formation, and thus alter cloud properties and their own deposition patterns. While the role of INA bacteria and fungi in atmospheric processes receives considerable attention, the numerical abundance and the capacity for ice nucleation in atmospheric microalgae is understudied. We isolated 81 strains of airborne microalgae from snow samples and determined their taxonomy by sequencing their ITS markers, 18S rRNA genes or 23S rRNA genes. We studied ice nucleation activity of airborne isolates, using droplet freezing assays, and their ability to withstand freezing. For comparison, we investigated 32 strains of microalgae from a culture collection, which were isolated from polar and temperate aqueous habitats. We show that 17% of isolates, which belonged to taxa Trebouxiphyceae, Chlorophyceae and Stramenopiles, were INA. A large fraction of INA strains (over 40%) had ice nucleation activity at temperatures ≥-6 °C. We found that 50% of aquatic microalgae were INA, but the majority were active at temperatures <-12 °C. Most INA compounds produced by microalgae were proteinaceous and associated with the cells. While there were no deleterious effects of freezing on the viability of airborne microalgae, some of the aquatic strains were killed by freezing. In addition, the effect of desiccation was investigated for the aquatic strains and was found to constitute a limiting factor for their atmospheric dispersal. In conclusion, airborne microalgae possess adaptations to atmospheric dispersal, in contrast to microalgae isolated from aquatic habitats. We found that widespread taxa of both airborne and aquatic microalgae were INA at warm, sub-zero temperatures (>-15 °C) and may thus participate in cloud and precipitation formation.